Hydrogel with Orthogonal Reactive Units: 2D and 3D Cross‐Linking Modulation. Issue 1 (17th November 2016) - Giustina, Gioia Della; Giulitti, Stefano; Brigo, Laura; Zanatta, Michele; Tromayer, Maximilian; Liska, Robert; Elvassore, Nicola; Brusatin, Giovanna
Abstract : In this work, an engineered hydrogel system with a 2D and 3D tunable cross‐linking degree is presented. A precise chemical design by the introduction of cross‐linkable units, having reaction orthogonality, allows to control the network formation both in time and space and to selectively alter the hydrogel physical properties. Hydrogel chemistry has been tailored in order to produce spatially controlled stiffness changes and drive cell morphology through mechanical cues. Elastic modulus rises by more than double after photocross‐linking, as shown by atomic force microscopy measurements. Biological response is also analyzed and stiffness‐dependent cell spreading and proliferation are verified. Different pattern geometries are successfully realized by UV lithography, allowing 2D cross‐linking modulation. Furthermore, 3D mechanical tuning at micro‐ and submicrometer scale by two‐photon polymerization makes this system a biologically relevant matrix to study cell functions and tissue development. Abstract : A hydrogel material with tailorable 2D and 3D cross‐linking degree by conventional UV lithography and 3D two‐photon direct laser writing technology is presented. Mechanical properties (e.g., stiffness) can be modulated to induce different cell behaviors: elongated cells and higher proliferation are evident on 2D stiff patterns compared to the less cross‐linked soft regions.